First report on two ostracod genera Loxoconcha Sars, 1866 (Loxoconchidae) and Xestoleberis Sars, 1866 (Xestoleberididae) along the coast of Vietam - Dung, Le Doan; Tsukagoshi, Akira (Academia Journal of Biology, 2019)
One survey was done with SCUBA diving in Ha Long Bay and Cat Ba Island, Northern Vietnam (December 2013) and another one at Nha Trang Bay Marine Protected Area, Nha Trang city, Central Vietnam and Phu Quoc Marine Protected Area, Kien Giang Province, Southern Vietnam (November 2014). Sixteen species of the genus Loxoconcha and fourteen species of the genus Xestoleberis were found and identified. Eight species of the genus Loxoconcha were identified in group A, three species in group B, two in group C and three unidentified. Meanwhile, twelve species of the genus Xestoleberis were classified in group A and two in group B according to phylogenetic groups. From geographical distribution of the pore groups of the species in two genera Loxoconcha and Xestoleberis showed that the fauna of these genera in Vietnam is close to those of southern part of Japanese Island Arc, i.e., from Amami Island to the Philippines and Australia rather than Japanese Island Arc faunas.